Migrants' savings, purchasing power parity, and the optimal duration of migration - Oded Stark; Christian Helmenstein; Yuri Yegorov (Institute for Advanced Studies (IHS), 1997)
If some of the returns to migration accrue from return migration, the optimal duration of migration may be shorter than the feasible duration of migration. We develop a model that provides and highlights conditions under which return migration takes place even though a reversal of the inter-country wage differential does not occur. In particular, we consider the higher purchasing power of savings (generated from work abroad) at home than abroad as a motive for return migration. Inter alia, our model produces a negative relationship between the optimal duration of migration and the purchasing power differential and in some (but not all) cases, a negative relationship between the optimal duration of migration and the wage abroad. In addition, and contrary to our prior anticipation, our utility maximization analysis suggests that East-West migration will tend to be temporary while inter-European Community (or intra-West European) migration will likely be permanent. – – Sofern die Vorteilhaftigkeit einer Auswanderungsentscheidung von einer späteren Rückkehr in das Herkunftsland beeinflusst wird, kann die optimale Aufenthaltsdauer im Zielland unter der maximal möglichen Aufenthaltsdauer liegen. Wir leiten Bedingungen ab, unter denen Auswanderung in Verbindung mit einer späteren Rückwanderung eine optimale Strategie darstellt, obwohl keine Umkehr des positiven Lohndifferentials zwischen dem Zielland und dem Hekunftsland erfolgt. Insbesondere untersuchen wir die Rolle einer höheren Kaufkraft von im Ausland akkumulierten Ersparnissen im Herkunftsland in ihrer Bedeutung für Remigration. Unter anderem besteht ein negative Beziehung zwischen der optimalen Aufenthaltsdauer und der Höhe des Kaufkraftdifferentials sowie in einigen (aber nicht allen) Fällen eine negative Beziehung zwischen der optimalen Aufenthaltsdauer und dem Lohnniveau im Zielland. Die Ergebnisse unseres Modelles deuten unerwarteterweise darauf hin, daß Ost-West-Wanderungen tendenziell temporärer Natur sein sollten, während Wanderungen innerhalb der Europäischen Union (bzw. innerhalb Westeuropas) tendenziell permanenten Charakter haben sollten.
Keywords: F22; J61; 330; return migration; migrants' savings; purchasing power differentials